Quantitative fluorescent PCR : a rapid approach to prenatal diagnostics of common autosomal aneuploidies - Pavlinić, Dinko (Array, 2008)
Summary: Autosomal trisomies account for more than 80 % of significant chromosomal disorders and are routinely detected by the cytogenetic analysis of cultivated amniotic fluid cells. However, this approach is time-consuming and requires a significant level of training and expertise. The main aim of our work was to introduce QF-PCR to our lab, a quicker, simpler and cheaper method. We also aimed to evaluate the usefulness of the chosen marker set in the Croatian population and the reliability and accuracy of the obtained results. STR loci from chromosomes 13, 18 and 21 were co-amplified, separated by capillary electrophoresis and analysed. Characteristic triplets and/or 2:1 patterns were detected for trisomic samples while normal samples were either homozygous or heterozygous. The tested set of loci showed high heterozygosity and therefore a good potential for analyzing the Croatian population. The results of QF-PCR were in full compliance with the cytogenetic analysis which was also performed for cultivated amniotic fluid cell samples